POLITENESS STRATEGIES IN DONALD TRUMP’S SPEECH AT REPUBLICAN NATIONAL CONVENTION 2016 / Nguyễn Tiến Đạt; NHDKH Assoc.Prof.Dr Hồ Ngọc Trung - Nguyễn, Tiến Đạt
The reason for writing the research lies in two points. The first one is to find out the politeness strategies and their functions in the speech of Donald Trump in Republican National Convention 2016. The second point is to apply the findings of the research to suggest measures to improve presentation skill of Vietnamese students. The research problem is politeness strategies in politeness theory by Brown and Levinson. The scope of the research is politeness strategies used in the speech of Donald Trump in Republican National Convention 2016. In this research, the author uses a pragmatic approach to a genre of discourse: political speeches. Within this domain, qualitative method is chosen as the main method to carry out the research because this study focuses on understanding a linguistic phenomenon, politeness strategy used in a formal speech. Besides, the author would like to also use quantitative method and statistical instrument in order to list all of the politeness strategies, their frequency. Donald Trump uses all four politeness strategies in his speech at Republican National Convention 2016. Among those strategies, positive politeness is mainly used and has the highest rate of use. The main reason for the difference in using rate lies in the function of each strategy. From the findings of the research, the author suggests to improve presentation skill of Vietnamese students via three measures. First of all, the author suggests improving English textbook and testing - assessment speaking skill/presentation skill. Secondly, the author suggests some speaking skill/presentation skill teaching methods/techniques. The last implication is suggestions for speaking skill/ presentation skill learning methods/techniques.